A Narrative Review of the Needs of Children in Foster and Kinship Care: Informing a Research Agenda. Issue 4 (7th December 2020) - Kemmis-Riggs, Jacqueline; McAloon, John
Abstract: As a result of maltreatment, children in care can present with a range of complex needs and challenges. In addition to direct clinical care commonly provided by paediatricians, psychiatrists, and clinical psychologists, the provision of knowledge and skills to foster and kinship carers have become modes of support common in responding to these needs and challenges. A narrative review of key systematic reviews and empirical research was conducted to assess the effectiveness of existing foster carer interventions. Results indicated a range of methodological characteristics that limit our ability to develop a sound, research-driven, evidence base. As a result, we remain limited in our knowledge about which treatments are effective, for which symptoms they are effective, and for which population subgroups they are most likely to be effective. This review provides a summary of identified needs and challenges in the delivery of foster carer interventions. It provides an account of current treatment components and offers a platform for the development and progression of a programme of research in an effort to advance knowledge in the area.